Kelsen és Montesquieu között : A hatalmi ágak megosztása és a demokrácia a 21. században - Olechowski, Thomas (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
This paper is the written version of the Ordinary Professorial Inaugural Lecture „Zwischen Kelsen und Montesquieu. Gewaltenteilung und Demokratie im 21. Jahrhundert” delivered at the University of Vienna on 27 March 2023. In his writings on democracy, Hans Kelsen initially rejected Montesquieu’s concept of the separation of powers and later only hesitantly recognised it. In fact, however, in the democracy of the 21st century, both the rule of the majority and the separation of powers are indispensable to guarantee the freedom of the individual. Both elements, however, are facing new challenges and threats that need to be recognised.